Application of Antibody Fragments Against Aβ With Emphasis on Combined Application With Nanoparticles in Alzheimer's Disease - Zhi-Ting Sun; Chi Ma; Guang-Jian Li; Xiang-Yu Zheng; Yi-Tong Hao; Yu Yang; Xu Wang (Frontiers Media S.A., 2021)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases and accumulating evidences suggest a key role of amyloid-β (Aβ) peptide in the pathogenesis of AD. According to the amyloid cascade hypothesis, the imbalance of producing and clearing Aβ is the beginning of neurodegeneration and dementia. Consequently, immunotherapy becomes popular through using antibodies against Aβ. However, many studies of monoclonal antibodies were stopped because adverse effects appeared or there were no evident benefits observed. Some antibody fragments have many advantages over monoclonal antibodies, such as small sizes, lack of the crystallizable fraction (Fc) and so on. There are three main antibody fragments, including single chain variable fragments (scFvs), Fab fragments and single-domain antibody fragments. Nanoparticles can facilitate the entry of drug molecules across the blood-brain barrier, making them become excellent carriers. Various kinds of nanoparticles have been applied in the treatment of AD. The combination of nanoparticles and antibody fragments against amyloid-β can be used in the diagnosis and treatment of Alzheimer's disease. In this review, we summarize the progress of antibody fragments against amyloid-β in AD, focusing on the combined application with nanoparticles in the diagnosis and treatment of AD.